2018
DOI: 10.1021/acschembio.8b00698
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel B-Cell Lymphoma 6 (BCL6) PROTAC To Provide Insight into Small Molecule Targeting of BCL6

Abstract: B-cell lymphoma 6 (BCL6) inhibition is a promising mechanism for treating hematological cancers but high quality chemical probes are necessary to evaluate its therapeutic potential. Here we report potent BCL6 inhibitors that demonstrate cellular target engagement and exhibit exquisite selectivity for BCL6 based on mass spectrometry analyses following chemical proteomic pulldown. Importantly, a proteolysis-targeting chimera (PROTAC) was also developed and shown to significantly degrade BCL6 in a number of The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 40 publications
2
110
0
Order By: Relevance
“…Further approaches to use BCL6 small molecule inhibitors as target binding ligand of proteolysis targeting chimeras (PROTACs) resulted in compounds that induce degradation of BCL6, albeit not to complete levels. However, also these PROTACs failed to induce enhanced anti-proliferative effects in vitro [19].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Further approaches to use BCL6 small molecule inhibitors as target binding ligand of proteolysis targeting chimeras (PROTACs) resulted in compounds that induce degradation of BCL6, albeit not to complete levels. However, also these PROTACs failed to induce enhanced anti-proliferative effects in vitro [19].…”
Section: Discussionmentioning
confidence: 91%
“…However, it remains not fully investigated whether BCL6 is relevant for tumor maintenance. A variety of BCL6 inhibitors have been previously reported, several of which have demonstrated that the BTB domain of BCL6 is amenable to targeting with peptide and small molecule inhibitors (reviewed in [18]) as well as PROTACs [19]. The BTB domain is required for interaction with co-repressor complex proteins to mediate transcriptional repression [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the gene IRF2 was identified in MM.1S cells, Pou class 2 homeobox-associating factor 1 and Bcl6 transcriptional repressor were identified in ly1 cells, C-C motif chemokine ligand 2 and IL8 were identified in HUVEC-C cells, TCF7 was identified in KOPT-K1 cells, HMGA2 was identified in U-87 cells, and INSM transcriptional repressor 1 was identified in H2171 cells. These detected TFs have previously been reported to serve important roles in the corresponding cell lines (44)(45)(46)(47)(48). notably, it was also observed that a small number of genes were super-loaded with Brd4 in multiple cell lines, particularly MYc and Bcl2-related protein a1 (Bcl2a1).…”
Section: Brd4 Super-enriched Regions or Genes In Each Cell Line Comprmentioning
confidence: 63%
“…18,19 Targets that have been shown to be degraded by PROTACs include members of bromodomain-containing proteins such as the BET proteins (Brd2, Brd3 and Brd4), [7][8][9]14,15,17,20,21 amongst other epigenetic protein classes; [22][23][24][25][26] protein kinases; 10,12,[27][28][29][30][31] as well as non-bromodomain and non-kinase target proteins. [32][33][34][35] Recent progress in understanding principles of PROTAC mode of action, and demonstration of applicability across different target classes, suggest that PROTACs have the potential to target new protein families, including proteins that are difficult to block using current approaches.…”
Section: Introductionmentioning
confidence: 99%